NUTS III as Decision-Making Vehicles for Diffusion and Implementation of Education for Entrepreneurship Programmes in the European Union: Some Lessons from the Portuguese Case - Francisco Banha; Adão Flores; Luís Serra Coelho (MDPI AG, 2022)
The questions of how Entrepreneurship Education (EE) initiatives can be successfully spread and what political structures can help with their implementation during compulsory school remain open. We will add to the literature by proposing that the scale of the NUTS III and its governance model/characteristics are ideal for carrying out initiatives related to EE in the EU and, thus, developing local entrepreneurship ecosystems. We will do so based on the evidence gathered from the case study of the Intermunicipal Community of Viseu Dão-Lafões. To underpin our main argument, we will explain the successful case of how the Intermunicipal Community of Viseu Dão-Lafões (a NUTS III) managed to become an exception in the Portuguese scenario when it comes to the funding, administrative articulation, and implementation of EE programmes for youths in the region.